Strategic plan for community service in Malang Universitas Terbuka distance learning program unit (UPBJJ-UT) lecturers - Niku, Elpipres (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
This research aims to analyze in depth the Strategic Plan for Community Service among Open University Lecturers. The approach used in this study is a qualitative approach, with a type of literature study and field research. And data collection techniques using interviews, observation, and documentation. The subject of this research is the lecturer as the main subject in UPBJJ-UT Malang. The research shows that the strategic plan for community service among UPBJJ-UT Malang lecturers, includes program preparation activities, preparation of resources and governance so that goals are achieved, and become a center of excellence for community service activities and services characterized by distance education. This is an obligation for lecturers to contribute to one of the elements of the Tri Dharma of Higher Education, so that lecturers have real benefits for society, seen as being able to bring up various new innovations that will produce published works. With the implementation of this community service-based program, it is a big homework for lecturers to follow up immediately.